Global burden of NAFLD 1990–2021 and projections to 2035: Results from the Global Burden of Disease study 2021 - Yuqin Mao; Jiqing Du; Baoguo Li; Jiong Wang; Shaoyan Xuan; Shu Yang; Zhihua Tang; Minxiu Wang (PLoS ONE, 2025)
Background Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease. The global burden of NAFLD is increasing. This study used the Global Burden of Disease (GBD) 2021 study data to assess the burden and development trends of NAFLD from 1990 to 2021. Methods The incidence, prevalence, death and disability-adjusted life years (DALYs) rates of NAFLD in geographic populations worldwide from 1990 to 2021 were extracted from the GBD 2021 study data. The global temporal trend of NAFLD from 1990 to 2021 was evaluated using estimated annual percentage change and age-standardized rate. The Bayesian age-period-cohort model was used to predict NAFLD burden future trends to 2035. Results The global age standardized incidence rate (ASIR) of NAFLD among the all-age population increased by 25% and the age standardized prevalence rate (ASPR) increased by 24%. The age standardized mortality rate (ASMR) and age standardized DALYs rate (ASDR) were relatively stable. Countries with middle socio-demographic index (SDI) had the highest ASIR and ASPR from 1990 to 2021, high-middle SDI and high SDI had the lowest ASMR and ASDR. North Africa and Middle East had the highest ASIR and ASPR in 2021, ASIR increased at the greatest rate in East Asia and Western Europe, ASPR increased at the greatest rate in Western Europe. In 2021, the highest number of incidence cases and incidence rates were in 20–24 years group, reflecting a tendency towards a younger onset of NAFLD. Conclusions The global burden of NAFLD has risen steadily from 1990 to 2021, and projections to 2035, placing enormous pressure on society. It is necessary to implement measures targeting risk factors such as high fasting plasma glucose and tobacco, including improving lifestyle, adjusting diet, and applying drug intervention.